Guarantee of legal trade against wages at PT. Gorontalo Citra Lestari - SITI MAGFIRA TOI (Universitas Negeri Gorontalo, 2019)
This research aims to find out how The Legal Protection of Workers' Wages in PT. Gorontalo Citrea Lestari. The type of research used in this paper is empirical research. This research uses a case approach, by conducting a review of cases related to the issues faced that have become court decisions that have had permanent powers. The results of this study show the Legal Protection of Workers' Wages in PT. Gorontalo Citra Lestari has not fully run optimally, this is proven by the violation of the law felt by workers. Preferably pt. Gorontalo Citra Lestari is more concerned with the protection of its workers by labor laws, and the protection of workers must be implemented to the maximum this creates a sense of security and comfort towards workers and does not cause things that are not desirable.